A photographic documentation of the development of Antarctic krill ( Euphausia superba ) from egg to early juvenile - Jia, Z; Virtue, P; Swadling, KM; Kawaguchi, S (Polar Biology, 2014)
Antarctic krill ( Euphausia superba ) is a keyspecies in Antarctic marine ecosystems, as well as animportant species in the Southern Ocean fishery. Here, weprovide the first detailed photographic documentation ofembryonic and larval development of Antarctic krill over a5-month developmental period under controlled laboratoryconditions. Developing embryos and larvae were photographedevery 3 h and every 5 days, respectively. Ourresults indicated a developmental time of approximately6 days for embryos and 138 days for larvae (0.5 Celsius degree). Thisstudy provided baseline biometry information for futureinvestigations of Antarctic krill development underchanging environmental conditions.